GENDER DIFFERENCES ON DIGITAL MARKETING TO BUSINESS PERFORMANCE - Fitriani, Lili (TRIKONOMIKA, 2025)
The rapid digital transformation has significantly altered business landscapes, particularly affecting Micro, Small, and Medium Enterprises (MSMEs) operations and performance. While digital marketing adoption is crucial for business sustainability, however gender-based differences in entrepreneurial behaviors and technology adoption patterns remain underexplored. Understanding how entrepreneurial orientation and market orientation influence digital marketing utilization among male and female entrepreneurs is essential for developing targeted business support strategies and enhancing the competitiveness of MSMEs in the digital economy. The results of this study indicate that female entrepreneurs exhibit stronger entrepreneurial orientation and market orientation, leading to a significant influence of both variables on the utilization of digital marketing and business performance. In contrast, for male entrepreneurs, entrepreneurial orientation does not influence the use of digital marketing and business performance. Additionally, market orientation does not affect the utilization of digital marketing but does impact business performance.